Charge carrier performance of phosphazene-based ionic liquids doped hole transport layer in organic light-emitting diodes - Mucur, Selin Piravadili; Canimkurbey, Betul; Kavak, Pelin; Akbas, Huseyin; Karadag, Ahmet (SPRINGER HEIDELBERG, 2020)
The enhancement of hole injection layers is strongly important issue for obtaining high-efficient and low-driving-voltage Organic Light-Emitting Devices (OLEDs). In this paper, we presented a comprehensive electroluminescence (EL) study of phosphazene-based ionic liquids (PzILs) used as a hole transport layer in solution-processed OLEDs. Charge transfer properties of PzILs were investigated by doping in poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) at different ratios (0.1, 0.2, 0.5, 1.0, 2.0). Previously synthesized four types of PzILs (namely PzIL1, PzIL2, PzIL3, and PzIL4) were prepared in de-ionized water with 10 mg/ml concentration, mixed with PEDOT:PSS and examined for their charge transport characteristics on OLED device performance due to their ionic nature. The device with PzIL1 exhibited the best performance with luminance 4185 cd/m(2) compared to other devices with and without PzILs. Further, Density Functional Theory (DFT) calculations and admittance spectroscopic analysis of OLEDs based on four types of PzILs were studied profoundly. Admittance spectroscopy has been used for revealing the carrier transport properties, mobility and the equivalent circuit modeling of the devices. Four types of PzILs OLEDs represented typical p-type transporting characteristics with moderate mobility up to 1.93 cm(2)/V.s.
Keywords: Organic light-emitting diodes (OLEDs); Phosphazene-based ionic liquids; PEDOT; PSS; Charge transfer; Admittance spectroscopic analysis; THIN-FILMS; HOST MATERIALS; CONDUCTIVITY; POLY(3,4-ETHYLENEDIOXYTHIOPHENE); CYCLOTRIPHOSPHAZENE; ENHANCEMENT; INTERFACE; ALIGNMENT; SOLVENTS; ENERGY; Materials Science; Physics